BMPs for sale!: Implications from a case study in BMP auctions - Smith, Craig M.; Leatherman, John C.; Peterson, Jeffrey M.; Crespi, John M.; Roe, Josh D. (My University, 2013)
Over the past several decades, there has been an increase in the use of market-based approaches for environmental policy. The purpose of this paper is three-fold: 1) to provide a review of the literature on auction-based approaches to environmental management, 2) to gain insight into the use and effectiveness of an alternative auction designs, and 3) to present considerations for enhancing the use of flexible auction approaches for future environmental application. Specifically, this paper describes how innovative BMP auctions were used to distribute conservation funding in a small watershed in east-central Kansas and offers insights into their overall cost-effectiveness. Overall, there were 61 bids for practices requesting a total of $98,524 in funding. Through the bid evaluation process, 46 of the bids were actually funded, which resulted in an estimated 2,901 tonnes of annual soil erosion reduction. This came at a total cost of $62,566. The lessons learned from the project can help guide future conservation programs seeking market-based solutions to bring about environmental benefits and researchers interested in analyzing the effectiveness of these mechanisms.
Keywords: Environmental management; Environmental policy; BMP auctions; Conservation; Market-based solutions